Zambia Economic Brief, December 2015 : Powering the Zambian Economy - World Bank Group (World Bank, Lusaka, 2016)
Zambia faces its toughest economic challenges in at least a decade. The economy has come under strain in 2015 as external headwinds and domestic pressures have intensified. The main domestic risks are threefold. Firstly, that the power crisis will worsen. Secondly, a deterioration of confidence in the economy, leading to further weakening of the currency and increased levels of inflation. Lastly, a bad harvest that serves to increase food prices and reduce rural and agricultural incomes, with the greatest impact falling on the poorest households. Commodity-exporting countries’ policy makers face increasing challenges across the globe. Zambia is no exception and must grapple with multiple challenges as the economy slows down. Strengthening the fiscal position and restoring fiscal buffers are necessary to increase confidence in the economy, reduce the need for costly borrowing, and build resilience against further exogenous shocks. Economic progress since 2000, driven by mining production and services, has substantially increased the demand for electricity in Zambia. Key to note is that an increase in tariffs to cost-reflective levels is necessary but not sufficient to increase private investment in electricity generation in Zambia. The new generation capacity and emergency measures for 2016 will help in mitigating the impact of the power crisis in the coming year, but global experience shows there is no substitute for effective planning. Particular efforts are needed to improve sector planning and the procurement processes for large power projects.